2020
DOI: 10.1007/s13197-020-04689-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Michelia alba oil against mould on brown rice and assessing the brain response using electroencephalogram (EEG)

Abstract: The objective of this study was to develop antifungal fragrant brown rice using the vapour phase of Michelia alba oil and to understand the effects of fragrant brown rice on consumer reactions using an electroencephalography (EEG) technique. The effect of M. alba oil vapour (300–900 µL/L) on the growth of moulds was studied in brown rice. Then, optimisation of the M. alba oil vapour (300–900 µL/L) was studied through sensory evaluation. Next,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…These findings are corroborated by one EEG study which reported increased alpha waves after lavender EO inhalation, suggesting a relaxing effect (Park et al, 2019 ). Moreover, three studies (Diego et al, 1998 ; Dimpfel et al, 2004 ; Songsamoe et al, 2020 ) showed a positive correlation between lavender EO inhalation and beta power increase, indicating arousal decrease; in the same study, arousal decline allowed the subjects to better perform sustained attention tasks. It is worth noting that Diego et al ( 1998 ), Dimpfel et al ( 2004 ), Park et al ( 2019 ) and Songsamoe et al ( 2020 ) also studied cognitive effects of lavender EO; however, these studies were not included in this systematic review because they were based on a within‐subject design.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…These findings are corroborated by one EEG study which reported increased alpha waves after lavender EO inhalation, suggesting a relaxing effect (Park et al, 2019 ). Moreover, three studies (Diego et al, 1998 ; Dimpfel et al, 2004 ; Songsamoe et al, 2020 ) showed a positive correlation between lavender EO inhalation and beta power increase, indicating arousal decrease; in the same study, arousal decline allowed the subjects to better perform sustained attention tasks. It is worth noting that Diego et al ( 1998 ), Dimpfel et al ( 2004 ), Park et al ( 2019 ) and Songsamoe et al ( 2020 ) also studied cognitive effects of lavender EO; however, these studies were not included in this systematic review because they were based on a within‐subject design.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, three studies (Diego et al, 1998 ; Dimpfel et al, 2004 ; Songsamoe et al, 2020 ) showed a positive correlation between lavender EO inhalation and beta power increase, indicating arousal decrease; in the same study, arousal decline allowed the subjects to better perform sustained attention tasks. It is worth noting that Diego et al ( 1998 ), Dimpfel et al ( 2004 ), Park et al ( 2019 ) and Songsamoe et al ( 2020 ) also studied cognitive effects of lavender EO; however, these studies were not included in this systematic review because they were based on a within‐subject design. Moreover, beta power is reported to be also related to less pronounced attentional blink (Gross et al, 2004 ; Shapiro et al, 2017 ), and this supports the hypothesis of a possible causal relation between lavender EO inhalation, arousal decrease and higher tonic attention performance.…”
Section: Discussionmentioning
confidence: 91%
“…The bioactivity of activity as an anti-microbial can be developed as a natural preservative. The essential oil of M. alba extended the shelf life of brown rice by four times compared to controls treated without essential oil [18,19].…”
Section: Anti-microbialmentioning
confidence: 94%
“…Bioactive compounds (e.g., linalool) isolated from M. alba have been approved as a natural food additive and are deliberated to be generally recognized as safe (GRAS) by the FDA as a synthetic flavoring substance and adjuvant in food for human consumption including as an ingredient in animal drugs, feeds, and related products [ 99 ]. In 2017, Songsamoe and colleagues developed antifungal fragrant brown rice using the vapor phase of M. alba oil [ 39 ]. As bioactive compounds in M. alba such as linalool, caryophyllene and β-elements may affect the sensory quality leading to an anti-stress effect [ 11 ], the researchers demonstrated that the application of M. alba oil in the vapor phase is capable of improving consumer acceptance and preference for cooked brown rice while significantly controlling the growth of A. flavus , i.e., molds in brown rice [ 35 ].…”
Section: Traditional Uses and Potential Application Of Mich...mentioning
confidence: 99%